Appropriate Dosing Regimens of Non-Vitamin K Antagonist Oral Anticoagulants for Treatment of Patients With Non-Valvular Atrial Fibrillation: An Evidence-Based Consideration - Zhao, Shujuan; Hong, Xuejiao; Cao, Jingjing; Cai, Haixia; Du, Song; Ma, Peizhi (Frontiers in Pharmacology, 2020)
Patients with non-valvular atrial fibrillation (NVAF) exhibit a high risk of stroke, which is associated with high mortality. Thus, stroke prevention is crucial for the overall management of NVAF. Two categories of drugs, vitamin K antagonist warfarin and non-vitamin K antagonist oral anticoagulants (NOACs), are clinically used to prevent NVAF-related stroke. In some circumstances, NOACs are superior to warfarin. However, NOACs selection for NVAF patients is affected by many factors, including individual patient characteristics, comorbidities, risk factors, or laboratory variables. This article summarizes the discrepancy in NOACs management with emphasis on the dosing regimens and influencing factors, such as stroke risk, age, body weight, renal function, gastrointestinal bleeding (GIB) risk, and combination of antiplatelet therapy, in order to identify individual groups with particular clinical characteristics who may obtain more benefit from a certain dosing regimen of NOACs. Determination of a particular subset of patient populations for the appropriate dose regimen of NOACs will help to achieve desired clinical outcomes. Furthermore, to compensate clinical evidence, we should place more emphasis on the findings of current clinical trials and supplement real-world data.